ENACTMENT AND ENFORCEMENT OF ADDITIONAL BY-LAWS IN RESIDENTIAL STRATA-TITLED PROPERTIES UNDER THE BUILDING MAINTENANCE AND STRATA MANAGEMENT ACT (CAP. 30C, 2008 REV. ED.) - NGUYEN THI MINH HANG (2020)
Bachelor's